2001
DOI: 10.2118/01-02-04
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Flooding and ASP-Chemical Methods for Enhanced Oil Recovery

Abstract: Chemical flooding methods hold particular attraction for recovering the "residual oil" left in the reservoir after waterflooding. This paper describes and compares the results for two promising methods, viz. micellar flooding and alkaline-surfactant-polymer (ASP) flooding processes. Both of these methods have been tested successfully in the field, notably micellar flooding. Laboratory results are described for micellar floods in consolidated sandstone cores as well as in unconsolidated sand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Previous research (Thomas and Ali 2001;Hirasaki et al 2008;Flaaten et al 2010) has shown that light-oil recovery can be improved by the application of AS flooding. This work focuses on the application of this technique for heavy oil (10,000 cp).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research (Thomas and Ali 2001;Hirasaki et al 2008;Flaaten et al 2010) has shown that light-oil recovery can be improved by the application of AS flooding. This work focuses on the application of this technique for heavy oil (10,000 cp).…”
Section: Introductionmentioning
confidence: 99%
“…Alkalis can react with the acids present in crude oil to form in-situ soaps. The soap molecules also act as surfaceactive agents and hence can reduce the requirement of synthetic surfactants (Thomas and Ali 2001;Martin and Oxley 1985). Surfactants, whether synthetic or in the form of soap molecules made by alkali, reduce interfacial tension between water and oil.…”
Section: Introductionmentioning
confidence: 99%
“…Light oil recovery can be enhanced by the application of alkali-surfactant-polymer (ASP) flooding (Thomas and Ali 2001;Hirasaki et al 2008;Flaaten et al 2008). Surfactants are organic molecules having a hydrophilic head and a hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%
“…Alkalis can react with the acids present in the crude oil to form in-situ soaps. The soap molecules also act as surface active agents and hence can reduce the requirement of synthetic surfactants (Thomas and Ali 2001;Martin and Oxley 1985). Surfactants, whether synthetic or soap molecules made by alkali, reduce interfacial tension between water and oil.…”
Section: Introductionmentioning
confidence: 99%
“…Alkalis can react with the acids present in the crude oil to form in-situ soaps. The soap molecules also act as surface active agents and hence can reduce the requirement of synthetic surfactants (Martin, 1985;Thomas, 2001;Hirasaki, 2008). Surfactants, whether synthetic or soap molecules made by alkali, reduce interfacial tension between water and oil.…”
Section: Introductionmentioning
confidence: 99%